Effect of Amblyomma cajennense Ticks on the Immune Response of BALB/c Mice and Horses - Castagnolli, Karina Carrao [UNESP]; Ferreira, Beatriz Rossetti; Franzin, Alessandra Mara; de Castro, Marcio Botelho; Juan Szabo, Matias Pablo (Blackwell Publishing, 2008)
This work evaluated the effect of the Amblyomma cajennense tick on the immune response of BALB/c mice and on horse lymph node cell proliferation. We observed that mice do not develop resistance to nymphs of this tick species and that lymphocyte proliferation of this host is inhibited by tick saliva, nymphal extract, or infestations. Horse lymph node cell proliferation is inhibited by tick saliva as well. Mice lymphocytes under the effect of tick saliva, nymphal extract, or infestations display a predominantly. p Th-2 cytokine production pattern. Observed results partially explain this tick's disease vectoring capacity and broad host range.
Keywords: Amblyomma cajennense; immune response; horse; BALB/c mice